Active Phase Fault-Tolerant Control of 12-Phase Permanent Magnet Synchronous Generator Controllable Rectifier System. Issue 3 (February 2020) - Wang, Lei; Yu, Zhongjun; Yi, Xinqiang
Abstract: The multi-phase permanent magnet synchronous generator controllable rectification system has the capability of fault-tolerant operation and high reliability, and is widely used in ship power systems. After a phase loss fault occurs in such a system, the DC current output from each rectifier bridge is unbalanced, and the DC voltage ripple coefficient increases. In this paper, from the perspective of power balance distribution of residual phase windings and the symmetrical operation of the system, the design of fault-tolerant control strategy is carried out with current equalization and DC voltage maintenance as the control target. After detecting the phase loss fault of the generator, the blocking fault corresponds to the trigger pulse of the rectifier bridge connected to the whole set of three-phase windings, and the remaining three rectifier bridges are connected in parallel to provide the DC voltage to the load, and the trigger angle of the remaining three sets of rectifier bridges is adjusted to balance the output DC current of each bridge. The simulation and experimental results of a 100kW 12-phase permanent magnet synchronous generator controlled rectifier system operating under normal, phase loss and fault tolerance conditions are compared and analysed. The designed control method can effectively reduce the DC current imbalance and improve the DC power supply quality.